Battery
The battery design with a dual-layer negative electrode active material structure, featuring a Li-alloying first layer and non-Li-alloying buffer layer, addresses the trade-off between energy density and safety in alloy-based batteries by preventing expansion into the electrolyte, enhancing both performance metrics.
Patent Information
- Application Number
- JP2022516856
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-24
- Filing Date
- 2021-02-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-02-12
AI Technical Summary
Conventional batteries using alloy-based negative electrode active materials face a trade-off between energy density and safety due to the large volume changes during lithium ion insertion and desorption reactions, which can lead to the alloy-based active material penetrating the solid electrolyte layer, causing loss of battery function.
A battery design with a negative electrode active material layer comprising a first layer that alloys with Li and a second layer that does not alloy with Li, acting as a buffer layer to prevent expansion into the electrolyte layer, combined with the use of carbon materials in the second layer to reduce expansion and improve safety.
This configuration allows for both increased energy density and improved safety by preventing the first active material from penetrating the electrolyte layer while maintaining high discharge capacity.
Smart Images

Figure 0007603237000002 
Figure 0007603237000003 
Figure 0007603237000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to batteries. [Background technology]
[0002] Carbon materials are mainly used as the negative electrode active material in the negative electrodes of batteries. In order to obtain a higher battery capacity, the use of alloy materials such as silicon as the negative electrode active material has been considered.
[0003] Patent Document 1 discloses an all-solid-state battery in which a mixed material of a solid electrolyte containing Li, P, and S, a carbon material as a negative electrode active material, and an alloy-based material as a negative electrode active material is used in a negative electrode active material layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-225187 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the prior art, it is desirable to achieve both energy density and safety. [Means for solving the problem]
[0006] The present disclosure relates to A positive electrode and A negative electrode; a solid electrolyte layer located between the positive electrode and the negative electrode; Equipped with the negative electrode has a negative electrode current collector and a negative electrode active material layer located between the negative electrode current collector and the solid electrolyte layer, the negative electrode active material layer includes a first active material layer and a second active material layer located between the first active material layer and the solid electrolyte layer, the first active material layer contains, as a first active material, a material that is alloyed with Li; the second active material layer contains a second active material and a solid electrolyte, and does not contain a material that is not alloyed with Li; Provide the battery. Effect of the Invention
[0007] According to the present disclosure, it is possible to achieve both energy density and safety. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of a battery according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a detailed configuration of the negative electrode. [Diagram 3] FIG. 3 is a cross-sectional view showing the configuration of a negative electrode in the first modification. [Figure 4] FIG. 4 is a cross-sectional view showing the configuration of a negative electrode in the second modification. [Diagram 5] FIG. 5 is a cross-sectional view showing the configuration of a negative electrode in the third modification. [Figure 6] FIG. 6 is a cross-sectional view showing the configuration of the negative electrode in Comparative Example 1. As shown in FIG. [Figure 7] FIG. 7 is a cross-sectional view showing the configuration of the negative electrode in Comparative Example 2. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Findings on which this disclosure is based) When an alloy-based active material is contained in a negative electrode, the alloy-based active material expands and contracts due to the insertion and desorption reactions of lithium ions, causing a large change in the volume of the negative electrode. If the particles of the alloy-based active material are large, the particles may penetrate the solid electrolyte layer, which is an insulating layer, as they expand. In this case, the battery will no longer function.
[0010] In particular, in solid-state batteries, the solid electrolyte layer and the negative electrode active material layer have a dense structure, so that there is almost no space to absorb the expansion of the negative electrode active material in the solid-state battery, and the expansion of the negative electrode active material is subject to stricter constraints than batteries using a liquid electrolyte.
[0011] One way to solve the above problem is to increase the thickness of the insulating solid electrolyte layer, but since the solid electrolyte layer does not contribute to the energy density of the battery, increasing the thickness of the solid electrolyte layer reduces the energy density of the battery.
[0012] As described above, in batteries using alloy-based active materials, there is a trade-off between energy density and safety, and it is therefore desirable to achieve both energy density and safety.
[0013] (Summary of one aspect of the present disclosure) The battery according to the first aspect of the present disclosure comprises: A positive electrode and A negative electrode; a solid electrolyte layer located between the positive electrode and the negative electrode; Equipped with the negative electrode has a negative electrode current collector and a negative electrode active material layer located between the negative electrode current collector and the solid electrolyte layer, the negative electrode active material layer includes a first active material layer and a second active material layer located between the first active material layer and the solid electrolyte layer, the first active material layer contains, as a first active material, a material that is alloyed with Li; The second active material layer contains a second active material and a solid electrolyte, and does not contain a material that alloys with Li.
[0014] According to the first aspect, the second active material layer functions as a buffer layer between the first active material layer and the electrolyte layer. As a result, it is possible to prevent the first active material from expanding and penetrating the electrolyte layer. In addition, since the first active material layer contains a material that is alloyed with Li, the energy density of the battery is increased. Therefore, according to this embodiment, it is possible to achieve both energy density and safety.
[0015] In the second embodiment of the present disclosure, for example, in the battery according to the first embodiment, the second active material may include a carbon material. Since the expansion rate of carbon materials during charging is relatively small, the use of a carbon material as the second active material can improve the safety of the battery.
[0016] In the third aspect of the present disclosure, for example, in the battery according to the second aspect, the carbon material may include graphite, which is suitable as the second active material because it has a smaller expansion rate during the lithium ion insertion reaction than an alloy-based active material.
[0017] In a fourth aspect of the present disclosure, for example, in the battery according to any one of the first to third aspects, the first active material may contain at least one selected from the group consisting of silicon, tin, and titanium. The use of such a material as the first active material can increase the energy density of the battery.
[0018] In a fifth aspect of the present disclosure, for example, in the battery according to any one of the first to fourth aspects, the first active material layer may be thinner than the second active material layer, which can further improve the safety of the battery.
[0019] In a sixth aspect of the present disclosure, for example, in the battery according to any one of the first to fifth aspects, the first active material layer may not contain the second active material. With this configuration, the discharge capacity of the first active material layer can be sufficiently ensured.
[0020] In a seventh aspect of the present disclosure, for example, in the battery according to the sixth aspect, the first active material layer does not need to contain the solid electrolyte. With this configuration, the discharge capacity of the first active material layer can be sufficiently ensured.
[0021] In an eighth aspect of the present disclosure, for example, in the battery according to any one of the first to seventh aspects, the solid electrolyte may have lithium ion conductivity. With this configuration, the lithium ion conductivity of the negative electrode active material layer can be increased.
[0022] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0023] (Embodiment) 1 is a cross-sectional view showing a schematic configuration of a battery 100 according to an embodiment. The battery 100 includes a positive electrode 220, a negative electrode 210, and an electrolyte layer 13.
[0024] The positive electrode 220 has a positive electrode active material layer 17 and a positive electrode current collector 18. The positive electrode active material layer 17 is disposed between the electrolyte layer 13 and the positive electrode current collector 18. The positive electrode active material layer 17 is in electrical contact with the positive electrode current collector 18.
[0025] The positive electrode current collector 18 is a member having a function of collecting power from the positive electrode active material layer 17. Examples of materials for the positive electrode current collector 18 include aluminum, aluminum alloys, stainless steel, copper, and nickel. The positive electrode current collector 18 may be made of aluminum or an aluminum alloy. The dimensions, shape, and the like of the positive electrode current collector 18 can be appropriately selected depending on the application of the battery 100.
[0026] The positive electrode active material layer 17 includes a positive electrode active material and a solid electrolyte. As the positive electrode active material, a material having a property of absorbing and releasing metal ions such as lithium ions can be used. As the positive electrode active material, a lithium-containing transition metal oxide, a transition metal fluoride, a polyanion material, a fluorinated polyanion material, a transition metal sulfide, a transition metal oxysulfide, a transition metal oxynitride, or the like can be used. In particular, when a lithium-containing transition metal oxide is used as the positive electrode active material, the manufacturing cost can be reduced and the average discharge voltage can be increased.
[0027] The positive electrode active material may contain Li and at least one element selected from the group consisting of Mn, Co, Ni, and Al. Examples of such materials include Li(NiCoAl)O2, Li(NiCoMn)O2, and LiCoO2.
[0028] The positive electrode active material has, for example, a particle shape. The particle shape of the positive electrode active material is not particularly limited. The particle shape of the positive electrode active material may be needle-like, spherical, oval-spherical, or scaly.
[0029] The median diameter of the particles of the positive electrode active material may be 0.1 μm or more and 100 μm or less. When the median diameter of the particles of the positive electrode active material is 0.1 μm or more, the positive electrode active material and the solid electrolyte can form a good dispersion state in the positive electrode 220. As a result, the charge and discharge characteristics of the battery 100 are improved. When the median diameter of the particles of the positive electrode active material is 100 μm or less, lithium diffusion within the particles of the positive electrode active material becomes fast. Therefore, the battery 100 can operate at a high output.
[0030] The solid electrolyte of the positive electrode 220 may be at least one selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte. The oxide solid electrolyte has excellent high potential stability. By using the oxide solid electrolyte, the charge / discharge efficiency of the battery 100 can be further improved.
[0031] In the positive electrode 220, the volume ratio "v1:100-v1" of the positive electrode active material to the solid electrolyte may be 30≦v1≦95. When 30≦v1 is satisfied, the energy density of the battery 100 is sufficiently ensured. Furthermore, when v1≦95 is satisfied, high-output operation is possible.
[0032] The thickness of the positive electrode 220 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 220 is 10 μm or more, the energy density of the battery 100 is sufficiently ensured. When the thickness of the positive electrode 220 is 500 μm or less, high-output operation is possible.
[0033] When the solid electrolyte contained in the positive electrode 220 is particulate (e.g., spherical), the median diameter of the solid electrolyte particles may be 100 μm or less. When the median diameter is 100 μm or less, the positive electrode active material and the solid electrolyte can form a good dispersion state in the positive electrode 220. This improves the charge / discharge characteristics of the battery 100.
[0034] In this specification, the term "median diameter" refers to the particle diameter when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.
[0035] The electrolyte layer 13 is located between the positive electrode 220 and the negative electrode 210. The electrolyte layer 13 is a layer including an electrolyte. The electrolyte is, for example, a solid electrolyte. The electrolyte layer 13 can be a solid electrolyte layer.
[0036] The electrolyte layer 13 may contain, as a solid electrolyte, at least one selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte.
[0037] The electrolyte layer 13 may have a multi-layer structure. In this case, the material composition of the layer in contact with the negative electrode 220 may be different from the material composition of the layer in contact with the positive electrode 220. The layer in contact with the negative electrode 220 may be made of a sulfide solid electrolyte having excellent reduction resistance. The layer in contact with the positive electrode 220 may be made of a halide solid electrolyte having excellent oxidation resistance.
[0038] The solid electrolyte contained in the electrolyte layer 13 has, for example, a particle shape. The particle shape is not particularly limited, and may be, for example, needle-like, spherical, or elliptical.
[0039] The thickness of the electrolyte layer 13 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 13 is 1 μm or more, it is possible to reliably prevent a short circuit between the positive electrode 220 and the negative electrode 210. When the thickness of the electrolyte layer 13 is 300 μm or less, it is possible to realize a high-output operation.
[0040] The negative electrode 210 includes a negative electrode active material layer 11 and a negative electrode current collector 12. The negative electrode active material layer 11 is disposed between the electrolyte layer 13 and the negative electrode current collector 12. The negative electrode active material layer 11 is in electrical contact with the negative electrode current collector 12.
[0041] The negative electrode current collector 12 is a member having a function of collecting power from the negative electrode active material layer 11. Examples of materials for the negative electrode current collector 12 include aluminum, aluminum alloy, stainless steel, copper, and nickel. The negative electrode current collector 12 may be made of nickel. The dimensions, shape, and the like of the negative electrode current collector 12 can be appropriately selected depending on the application of the battery 100.
[0042] 2 is a cross-sectional view showing a detailed configuration of the negative electrode 210. The negative electrode active material layer 11 includes a first active material layer 150 and a second active material layer 160. The second active material layer 160 is located between the first active material layer 150 and the electrolyte layer 13. The first active material layer 150 includes a material that is alloyed with Li as a first active material 31. The second active material layer 160 includes a second active material 32 and a solid electrolyte 33, and does not include a material that is alloyed with Li. The first active material 31 is unevenly distributed in the vicinity of the negative electrode current collector 12.
[0043] When the negative electrode active material layer 11 has the above structure, the following effects can be obtained. That is, even if the first active material 31 contained in the first active material layer 150 expands during the lithium ion insertion reaction, the second active material layer 160, which does not contain a material that is alloyed with Li, functions as a buffer layer between the first active material layer 150 and the electrolyte layer 13. As a result, it is possible to prevent the first active material 31 from expanding and penetrating the electrolyte layer 13. In addition, since the first active material layer 150 contains a material that is alloyed with Li, the energy density of the battery 100 is increased. Therefore, according to this embodiment, it is possible to achieve both energy density and safety.
[0044] "Does not contain a material that alloys with Li" means that a material that alloys with Li is not intentionally added. For example, when the mass of the material that alloys with Li is 1% or less with respect to the total mass of the active material contained in the second active material layer 160, it is considered that the material that alloys with Li is not intentionally added to the second active material layer 160.
[0045] In the present embodiment, the first active material layer 150 is in contact with the negative electrode current collector 12. However, the first active material layer 150 may be separated from the negative electrode current collector 12. Another layer may be provided between the first active material layer 150 and the negative electrode current collector 12. The first active material layer 150 is also in contact with the second active material layer 160. However, the first active material layer 150 may be separated from the second active material layer 160. Another layer may be provided between the first active material layer 150 and the second active material layer 160. The second active material layer 160 is in contact with the electrolyte layer 13.
[0046] Both the first active material 31 and the second active material 32 have the characteristics of occluding and releasing lithium ions. The theoretical capacity (unit: mAh / g) of the first active material 31 is larger than the theoretical capacity of the second active material 32. The expansion rate (volume expansion rate) of the first active material 31 during charging is larger than the expansion rate of the second active material 32 during charging.
[0047] The first active material 31 includes, for example, at least one selected from the group consisting of silicon, tin, and titanium. These are materials that alloy with Li, and all have a higher theoretical capacity than carbon materials. If these materials are used as the first active material 31, the energy density of the battery 100 can be increased. The material that alloys with Li is typically a metal or a semi-metal. The metal or semi-metal may be a single substance. It is not essential that the material that alloys with Li is a single metal or semi-metal. The material that alloys with Li may be a compound containing an element that alloys with Li. Examples of such compounds include silicon oxide represented by SiOx (0 < x < 2), tin oxide represented by SnO or SnO2, and the like.
[0048] The second active material 32 may be at least one selected from the group consisting of carbon materials, metal materials, oxides, nitrides, tin compounds, silicon compounds, and titanium compounds, excluding materials that are alloyed with Li. 12 ) can be used as the second active material 32. The metal material may be a single metal or an alloy. An example of the metal material is lithium metal. An example of the carbon material is graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, amorphous carbon, and the like. Since the expansion rate of the carbon material during charging is relatively small, the safety of the battery 100 can be improved by using the carbon material as the second active material 32. The second active material 32 typically includes graphite. Graphite is suitable as the second active material 32 because it has a smaller expansion rate during the lithium ion insertion reaction than alloy-based active materials.
[0049] "Alloy-based active material" refers to an active material that is alloyed with lithium. "Alloy-based material" refers to a material that is alloyed with lithium.
[0050] Both the first active material 31 and the second active material 32 may have a particulate shape. The particles of the first active material 31 and the particles of the second active material 32 may have a spherical, oval spherical, fibrous or scaly shape.
[0051] In the present embodiment, the first active material layer 150 contains both the first active material 31 and the second active material 32. This makes it possible to reduce the difference in expansion coefficient between the first active material layer 150 and the second active material layer 160 due to charging and discharging. In the first active material layer 150, the ratio (M2 / M1) of the mass M2 of the second active material 32 to the mass M1 of the first active material 31 is, for example, in the range of more than 0 and not more than 20. The mass M1 of the first active material 31 is the mass when elements (such as oxygen) other than elements that are alloyed with Li are ignored.
[0052] The solid electrolyte 33 is also contained in the first active material layer 150. With this configuration, it is possible to improve the ionic conductivity of the first active material layer 150. The composition of the solid electrolyte contained in the first active material layer 150 may be the same as or different from the composition of the solid electrolyte contained in the second active material layer 160.
[0053] The second active material layer 160 may contain, as the negative electrode active material, only materials other than the material that is alloyed with Li. With such a configuration, the safety of the battery 100 is further improved.
[0054] The thickness of each of the first active material layer 150 and the second active material layer 160 is not particularly limited. According to the example of FIG. 2, the first active material layer 150 and the second active material layer 160 have, for example, the same thickness. However, the first active material layer 150 may be thicker than the second active material layer 160. The first active material layer 150 may be thinner than the second active material layer 160.
[0055] There is no particular limitation on the discharge capacity of each of the first active material layer 150 and the second active material layer 160. The first active material layer 150 and the second active material layer 160 have, for example, the same discharge capacity.
[0056] The solid electrolyte 33 has lithium ion conductivity. When the solid electrolyte 33 is contained in the negative electrode active material layer 11, the lithium ion conductivity of the negative electrode active material layer 11 can be increased.
[0057] As the solid electrolyte 33, at least one selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte can be used.
[0058] Sulfide solid electrolytes include Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, and Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12These can be used in combination with LiX, Li2O, MO q , Li p MO q In this case, the element X in "LiX" is at least one element selected from the group consisting of F, Cl, Br, and I. q " and "Li p MO q "The element M is at least one element selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe, and Zn. q " and "Li p MO q " In this equation, p and q are independent natural numbers.
[0059] Examples of oxide solid electrolytes include NASICON-type solid electrolytes such as LiTi2(PO4)3 and its elemental substitutes, (LaLi)TiO3-based perovskite-type solid electrolytes, and Li 14 ZnGeO 16 , Li4SiO4, LiGeO4 and their elemental substitutions, LISICON-type solid electrolytes, Li7La3Zr2O 12 Garnet-type solid electrolytes, such as those typified by their elemental substitution products, Li3N and its H-substituted products, Li3PO4 and its N-substituted products, and glasses or glass ceramics in which materials such as Li2SO4 and Li2CO3 are added to a base material containing Li-BO compounds such as LiBO2 and Li3BO3 can be used.
[0060] As the polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound may have an ethylene oxide structure. By having an ethylene oxide structure, the polymer compound can contain a large amount of lithium salt, so that the ion conductivity can be further increased. As the lithium salt, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be used. As the lithium salt, one type of lithium salt selected from these may be used alone, or a mixture of two or more types of lithium salts selected from these may be used.
[0061] As the complex hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used.
[0062] The halide solid electrolyte is a solid electrolyte containing a halogen. The halide solid electrolyte is represented, for example, by the following composition formula (1). In the composition formula (4), α, β, and γ are each independently greater than 0. M includes at least one element selected from the group consisting of metal elements and semimetal elements other than Li. X includes at least one element selected from the group consisting of F, Cl, Br, and I.
[0063] Li α M β X γ (1)
[0064] Metalloid elements include B, Si, Ge, As, Sb, and Te. Metal elements include all elements in groups 1 to 12 of the periodic table except hydrogen, and all elements in groups 13 to 16 except B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se. Metal elements are a group of elements that can become cations when they form inorganic compounds with halogens or halogen compounds.
[0065] Examples of halide solid electrolytes that can be used include Li3YX6, Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, and Li3(Al,Ga,In)X6.
[0066] In this disclosure, when an element in a formula is expressed as "(Al, Ga, In)", this notation indicates at least one element selected from the group of elements in the parentheses. That is, "(Al, Ga, In)" is synonymous with "at least one element selected from the group consisting of Al, Ga, and In". The same applies to other elements. Halide solid electrolytes exhibit excellent ionic conductivity.
[0067] The solid electrolyte 33 may be an inorganic solid electrolyte. Since the inorganic solid electrolyte has excellent electrochemical stability, it is suitable for the solid electrolyte 33. As described above, examples of the inorganic solid electrolyte include a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a complex hydride solid electrolyte. The solid electrolyte 33 may contain a sulfide solid electrolyte or may be made of a sulfide solid electrolyte. Since the sulfide solid electrolyte has excellent reduction resistance, it is suitable as a solid electrolyte used in the negative electrode active material layer 11. Since the sulfide solid electrolyte is highly flexible, if the sulfide solid electrolyte is contained in the negative electrode active material layer 11, the sulfide solid electrolyte may absorb the expansion and contraction of the alloy-based active material.
[0068] The first active material 31 and the second active material 32 may each have a particle shape. Hereinafter, the term “negative electrode active material particles” refers to one or both of the first active material 31 particles and the second active material 32 particles.
[0069] The median diameter of the particles of the negative electrode active material may be 0.1 μm or more and 100 μm or less. When the median diameter of the particles of the negative electrode active material is 0.1 μm or more, the particles of the negative electrode active material and the solid electrolyte can form a good dispersion state in the negative electrode 210. This improves the charge / discharge characteristics of the battery 100. Furthermore, when the median diameter of the particles of the negative electrode active material is 100 μm or less, lithium diffusion within the particles of the negative electrode active material becomes fast. Therefore, the battery 100 can operate at a high output.
[0070] The median diameter of the particles of the negative electrode active material may be larger than the median diameter of the particles of the solid electrolyte 33 contained in the negative electrode 210. This allows the negative electrode active material and the solid electrolyte 33 to be well dispersed.
[0071] When the volume ratio of the negative electrode active material to the solid electrolyte 33 in the negative electrode 210 is expressed as "v2:100-v2", the volume ratio v2 of the negative electrode active material may satisfy 30≦v2≦95. When 30≦v2 is satisfied, the energy density of the battery 100 is sufficiently ensured. Furthermore, when v2≦95 is satisfied, high-output operation is possible.
[0072] The thickness of the negative electrode 210 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 210 is 10 μm or more, the energy density of the battery 100 is sufficiently ensured. When the thickness of the negative electrode 210 is 500 μm or less, high-output operation is possible.
[0073] At least one of the positive electrode active material layer 17, the electrolyte layer 13, and the negative electrode active material layer 11 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.
[0074] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include cyclic carbonate ester solvents, chain carbonate ester solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, and fluorine solvents. Examples of the cyclic carbonate ester solvents include ethylene carbonate, propylene carbonate, and butylene carbonate. Examples of the chain carbonate ester solvents include dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate. Examples of the cyclic ether solvents include tetrahydrofuran, 1,4-dioxane, and 1,3-dioxolane. Examples of the chain ether solvents include 1,2-dimethoxyethane and 1,2-diethoxyethane. Examples of the cyclic ester solvents include γ-butyrolactone. Examples of the chain ester solvents include methyl acetate. Examples of the fluorine solvent include fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, and fluorodimethylene carbonate. As the non-aqueous solvent, one type of non-aqueous solvent selected from these may be used alone, or a mixture of two or more types of non-aqueous solvents selected from these may be used. The non-aqueous electrolyte may contain at least one type of fluorine solvent selected from the group consisting of fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, and fluorodimethylene carbonate.
[0075] Examples of the lithium salt include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), and LiC(SO2CF3)3. As the lithium salt, one type of lithium salt selected from these may be used alone, or a mixture of two or more types of lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 to 2 mol / liter.
[0076] The gel electrolyte may be a polymer material containing a non-aqueous electrolyte solution. The polymer material may be at least one selected from the group consisting of polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, and a polymer having an ethylene oxide bond.
[0077] The cations constituting the ionic liquid may be aliphatic chain quaternary salts such as tetraalkylammonium and tetraalkylphosphonium, aliphatic cyclic ammoniums such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, and piperidiniums, and nitrogen-containing heterocyclic aromatic cations such as pyridiniums and imidazoliums. The anions constituting the ionic liquid may be PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , C(SO2CF3)3 - The ionic liquid may contain a lithium salt.
[0078] At least one of the positive electrode active material layer 17, the electrolyte layer 13, and the negative electrode active material layer 11 may contain a binder for the purpose of improving the adhesion between particles. The binder is used to improve the binding property of the material constituting the electrode. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, and carboxymethyl cellulose. The binder may be a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. Two or more of these materials may be mixed and used as the binder.
[0079] At least one of the positive electrode active material layer 17 and the negative electrode active material layer 11 may contain a conductive assistant for the purpose of increasing electronic conductivity. Examples of the conductive assistant include graphites such as natural graphite or artificial graphite, carbon blacks such as acetylene black and ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene. When a carbon conductive assistant is used, costs can be reduced.
[0080] When the battery 100 of the present embodiment is an all-solid-state battery, the battery 100 does not contain an electrolytic solution, a gel electrolyte, or an ionic liquid.
[0081] Battery 100 in this embodiment can be configured as batteries of various shapes, such as a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, and a laminated type.
[0082] The negative electrode active material layer 11 may be formed by a wet method, a dry method, or a combination of a wet method and a dry method. In the wet method, a slurry containing raw materials is applied onto the negative electrode current collector 12. In the dry method, powder of the raw materials is compression molded together with the negative electrode current collector 12. The positive electrode active material layer 17 can also be formed by these methods.
[0083] 3 is a cross-sectional view showing the configuration of the negative electrode 211 in Modification 1. The negative electrode active material layer 11 has a first active material layer 151 and a second active material layer 161. The first active material layer 151 is thinner than the second active material layer 161. With such a configuration, the safety of the battery 100 can be further improved. When the thickness of the first active material layer 151 is T1 and the thickness of the second active material layer 161 is T2, the ratio T1 / T2 is in the range of 1 / 2 to 1 / 20, in one example.
[0084] The thickness of each layer may be the average value of a plurality of arbitrary points in a cross section including the center of gravity when the battery 100 is viewed in plan.
[0085] The materials contained in the first active material layer 151 and the second active material layer 161 are as described with reference to FIG.
[0086] FIG. 4 is a cross-sectional view showing the configuration of the negative electrode 212 in Modification 2. The negative electrode active material layer 11 has a first active material layer 152 and a second active material layer 161. The first active material layer 152 does not include the second active material 32. The first active material layer 152 may include only the first active material 31 as the negative electrode active material. With this configuration, the discharge capacity of the first active material layer 152 can be sufficiently ensured. This contributes to improving the energy density of the battery 100.
[0087] "Not including the second active material 32" means that the second active material 32 is not intentionally added.
[0088] In this modification as well, the first active material layer 152 is thinner than the second active material layer 161. Therefore, the negative electrode 212 has an excellent balance between energy density and safety.
[0089] FIG. 5 is a cross-sectional view showing the configuration of the negative electrode 213 in Modification 3. The negative electrode active material layer 11 has a first active material layer 153 and a second active material layer 161. The first active material layer 153 contains a first active material 31 and does not contain a solid electrolyte 33. The first active material layer 152 may contain only the first active material 31 as the negative electrode active material. With this configuration, the discharge capacity of the first active material layer 153 can be sufficiently ensured. This contributes to improving the energy density of the battery 100.
[0090] In this modification, the first active material layer 153 may be formed by forming a film of an alloy-based active material by a dry method on the surface of the negative electrode current collector 12. Examples of the dry method include vapor deposition and sputtering.
[0091] "Does not contain solid electrolyte 33" means that solid electrolyte 33 is not intentionally added.
[0092] In this modification as well, the first active material layer 153 is thinner than the second active material layer 161. Therefore, the negative electrode 213 has an excellent balance between energy density and safety. EXAMPLES
[0093] Hereinafter, the present disclosure will be described in detail using examples and comparative examples.
[0094] [Preparation of sulfide solid electrolyte] In a glove box in an Ar atmosphere with a dew point of -60°C or less, Li2S and P2S5 were weighed out to a molar ratio of Li2S:P2S5=75:25. These were ground and mixed in a mortar to obtain a mixture. Then, the mixture was milled at 510 rpm for 10 hours using a planetary ball mill (Fritsch, P-7 type) to obtain a glassy solid electrolyte. The glassy solid electrolyte was heat-treated in an inert atmosphere at 270°C for 2 hours. As a result, a powder of Li2S-P2S5, which is a glass-ceramic sulfide solid electrolyte, was obtained.
[0095] <<Example 1>> [Preparation of Material A1 for First Active Material Layer] In a glove box in an Ar atmosphere with a dew point of -60°C or less, graphite and Si were mixed in a mortar in a mass ratio of 4:1 to obtain a mixture. Then, the mixture of graphite and Si was mixed with a sulfide solid electrolyte in a mass ratio of 7:3. Thus, material A1 was obtained. Graphite and Si were used in powder form.
[0096] [Preparation of material B1 for second active material layer] Graphite and a sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less, thereby obtaining material B1.
[0097] [Preparation of secondary battery] The following steps were carried out using material A1, material B1, a sulfide solid electrolyte, and copper foil (thickness 12 μm).
[0098] First, 3 mg of the sulfide solid electrolyte, 5 mg of the material B1, and 5 mg of the material A1 were laminated in this order in an insulating outer cylinder, and these were press-molded at a pressure of 360 MPa to obtain a laminate of a negative electrode active material layer and an electrolyte layer.
[0099] Next, a copper foil was laminated on the layer of Material A1, and the laminate was molded under pressure at 360 MPa to obtain a laminate of a negative electrode current collector, a negative electrode active material layer, and an electrolyte layer.
[0100] Next, metal In (thickness 200 μm), metal Li (thickness 300 μm), and metal In (thickness 200 μm) were laminated on the electrolyte layer in this order, and these were press-molded at a pressure of 80 MPa to produce a laminate consisting of a positive electrode, an electrolyte layer, and a negative electrode.
[0101] Stainless steel current collectors were then placed on the top and bottom of the laminate, and current collecting leads were attached to the current collectors.
[0102] Finally, the insulating outer cylinder was sealed using an insulating ferrule to isolate the inside of the insulating outer cylinder from the outside atmosphere, thereby producing the battery of Example 1. The negative electrode of the battery of Example 1 had the structure described with reference to FIG.
[0103] <<Example 2>> [Preparation of Material A2 for First Active Material Layer] In a glove box in an Ar atmosphere with a dew point of -60°C or less, graphite and Si were mixed in a mortar in a mass ratio of 1:1 to obtain a mixture. Then, the mixture of graphite and Si was mixed with a sulfide solid electrolyte in a mass ratio of 7:3. Thus, material A2 was obtained.
[0104] [Preparation of material B2 for second active material layer] Graphite and a sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less, thereby obtaining material B2.
[0105] [Preparation of secondary battery] The battery of Example 2 was fabricated in the same manner as Example 1, except that 8 mg of material B2 was used instead of 5 mg of material B1, and 2 mg of material A2 was used instead of 5 mg of material A1. The negative electrode of the battery of Example 2 had the structure described with reference to FIG.
[0106] <<Example 3>> [Preparation of Material A3 for First Active Material Layer] In a glove box in an Ar atmosphere with a dew point of −60° C. or less, Si and a sulfide solid electrolyte were mixed in a mass ratio of 7:3 to obtain material A3.
[0107] [Preparation of material B3 for second active material layer] Graphite and a sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less, thereby obtaining material B3.
[0108] [Preparation of secondary battery] The battery of Example 3 was fabricated in the same manner as Example 1, except that 9 mg of material B3 was used instead of 5 mg of material B1, and 1 mg of material A3 was used instead of 5 mg of material A1. The negative electrode of the battery of Example 3 had the structure described with reference to FIG.
[0109] <<Example 4>> [Preparation of Material A4 for First Active Material Layer] In a glove box in an Ar atmosphere with a dew point of −60° C. or less, only Si was prepared as material A4.
[0110] [Preparation of material B4 for second active material layer] Graphite and a sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less, thereby obtaining material B4.
[0111] [Preparation of secondary battery] The battery of Example 4 was fabricated in the same manner as Example 1, except that 9 mg of material B4 was used instead of 5 mg of material B1, and 1 mg of material A4 was used instead of 5 mg of material A1. The negative electrode of the battery of Example 4 had the structure described with reference to FIG.
[0112] <<Comparative Example 1>> [Preparation of material a1 for first active material layer] Graphite and a sulfide solid electrolyte were mixed in a mass ratio of 7:3 in a glove box in an Ar atmosphere with a dew point of −60° C. or less, thereby obtaining a material a1.
[0113] [Preparation of material b1 for second active material layer] In a glove box in an Ar atmosphere with a dew point of -60°C or less, graphite and Si were mixed in a mortar in a mass ratio of 4:1 to obtain a mixture. Then, the mixture of graphite and Si was mixed with a sulfide solid electrolyte in a mass ratio of 7:3. Thus, material b1 was obtained.
[0114] [Preparation of secondary battery] A battery of Comparative Example 1 was produced in the same manner as in Example 1, except that 5 mg of material b1 was used instead of 5 mg of material B1, and 5 mg of material a1 was used instead of 5 mg of material A1.
[0115] 6 is a cross-sectional view showing the configuration of a negative electrode 300 of a battery in Comparative Example 1. The negative electrode 300 has a negative electrode current collector 312 and a negative electrode active material layer 311. The negative electrode active material layer 311 has a first active material layer 350 and a second active material layer 360. The negative electrode current collector 312, the first active material layer 350, and the second active material layer 360 are laminated in this order. The first active material layer 350 contains only graphite as the negative electrode active material. The second active material layer 360 contains graphite and Si as the negative electrode active materials.
[0116] <<Comparative Example 2>> [Preparation of material c1 for negative electrode active material layer] In a glove box in an Ar atmosphere with a dew point of -60°C or less, graphite and Si were mixed in a mortar in a mass ratio of 9:1 to obtain a mixture. Then, the mixture of graphite and Si was mixed with a sulfide solid electrolyte in a mass ratio of 7:3. Thus, material c1 was obtained.
[0117] [Preparation of secondary battery] A battery of Comparative Example 2 was produced in the same manner as in Example 1, except that 10 mg of material c1 was used instead of 5 mg of material B1 and 5 mg of material A1.
[0118] 7 is a cross-sectional view showing the configuration of a negative electrode 301 of a battery in Comparative Example 2. Anode 301 has a negative electrode current collector 312 and a negative electrode active material layer 311. Anode active material layer 311 is provided on anode current collector 312. Anode active material layer 311 contains graphite and Si as anode active materials. Graphite and Si are uniformly distributed in anode active material layer 311.
[0119] [Charge / discharge test] Charge / discharge tests were carried out under the following conditions using 10 batteries each of Examples 1 to 4, Comparative Examples 1 and 2. The theoretical capacities of the batteries of the Examples and Comparative Examples were the same.
[0120] The battery was placed in a thermostatic chamber at 25°C.
[0121] The battery was charged at a constant current of 380 μA, which corresponds to a 0.05 C rate (20 hour rate) relative to the theoretical capacity of the battery, and charging was terminated at a voltage of −0.62 V.
[0122] Next, the battery was discharged at a constant current of 380 μA, which corresponds to a 0.05 C rate (20 hour rate), and the discharge was terminated at a voltage of 1.9 V.
[0123] As described above, the initial discharge capacity of 10 cells of each of Examples 1 to 4, Comparative Example 1 and Comparative Example 2 was measured. The average value of the initial discharge capacity was calculated as the initial average discharge capacity, and the ratio of the initial average discharge capacity to the theoretical capacity was calculated. The results are shown in Table 1. Note that some of the batteries of Comparative Example 1 and Comparative Example 2 lost their battery function during charging. The number of batteries that lost their function is also shown in Table 1.
[0124] [Table 1]
[0125] <<Considerations>> As shown in Table 1, the expected theoretical capacity was obtained in all the batteries of the examples and comparative examples. This indicates that the arrangement of Si, which is an alloy-based active material, does not affect the discharge capacity.
[0126] None of the batteries of Examples 1 to 4 lost function during charging. The reason for this is believed to be that Si, which has a large expansion coefficient, was unevenly distributed near the negative electrode current collector, and no alloy-based active material was present near the electrolyte layer. It is believed that the second active material layer, which did not contain the alloy-based active material, existed between the electrolyte layer and the first active material layer, which contained the alloy-based active material, and the second active material layer functioned as a buffer material, so that the expanded alloy-based active material did not penetrate the electrolyte layer, and charging and discharging proceeded normally.
[0127] In contrast, some of the batteries of Comparative Examples 1 and 2 lost their function during charging. In the batteries of Comparative Examples, Si, which is an alloy-based active material, was present near the electrolyte layer. Therefore, it is presumed that the alloy-based active material expanded due to lithium ions being inserted into Si during charging, and the expanded alloy-based active material penetrated the electrolyte layer, causing an internal short circuit between the alloy-based active material and the lithium-indium alloy, which is the positive electrode active material. [Industrial Applicability]
[0128] The battery of the present disclosure can be used, for example, as an all-solid-state lithium secondary battery.
Claims
1. A positive electrode and A negative electrode; a solid electrolyte layer located between the positive electrode and the negative electrode; Equipped with the negative electrode has a negative electrode current collector and a negative electrode active material layer located between the negative electrode current collector and the solid electrolyte layer, the negative electrode active material layer includes a first active material layer and a second active material layer located between the first active material layer and the solid electrolyte layer, the first active material layer contains, as a first active material, a material that is alloyed with Li; the second active material layer contains a second active material and a solid electrolyte, and does not contain a material that alloys with Li; The first active material layer is thinner than the second active material layer. battery.
2. The second active material includes a carbon material.
10. The battery of claim 1.
3. The carbon material includes graphite.
3. The battery of claim 2.
4. The first active material includes at least one selected from the group consisting of silicon, tin, and titanium; The battery of any one of claims 1 to 3.
5. The first active material layer does not contain the second active material. The battery of any one of claims 1 to 4.
6. The first active material layer does not contain the solid electrolyte.
6. The battery of claim 5.
7. The solid electrolyte has lithium ion conductivity. The battery of any one of claims 1 to 6.
8. When the first active material layer has a thickness T1 and the second active material layer has a thickness T2, the ratio T1 / T2 is in the range of 1 / 2 to 1 / 20. The battery of any one of claims 1 to 7.
Citation Information
Patent Citations
Lithium ion cell
JP2008305746A
Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2012022794A
Laminate for all-solid secondary battery
JP2016225187A
All-solid battery
JP2019160407A
